The Mycteridae, Boridae, Pythidae, Pyrochroidae, and Salpingidae (Coleoptera: Tenebrionoidea) of the Maritime Provinces of Canada. Zootaxa, 1250, 37–51. (ERRATUM) - Majka, C.g. (Zootaxa, 2006)
In the article, figures 4 and 5 were unfortunately reversed. The legend for figure 4 (on page 44) corresponds with the map printed on page 45, and the legend for figure 5 (on page 45) corresponds with the map printed on page 44.